What Becomes of the Damned: Annihilationism Consistent with Nonexistent Objects - Shields, R. A. J. (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2024)
Annihilationism provides a fruitful point of contact between philosophers and theologians for further reflection on nonexistence. In this paper I articulate a key commitment of annihilationism; namely, that some persons cease to exist. Such a commitment, I argue, amounts to the claim that some persons exist at time t and then do not exist at t+1, become ‘annihilated objects.’ Claims about annihilated objects induct the annihilationist into a wider realism/anti-realism debate about nonexistent objects. I survey some major viewpoints in this debate. I then draw out some implications for each view for the annihilationist’s commitment to annihilated objects. I show that annihilationism is consistent with some forms of realism and anti-realism and inconsistent with others.